Who Does Report Past-Life Memories? Claimers’ Profile, Religiosity/Spirituality and Impact on Happiness and Mental Health - Carvalho, Sandra Maciel de (The international journal for the psychology of religion, 2025)
Religious/spiritual beliefs such as reincarnation are prevalent in many cultures. Although there have been studies of claims of past-life memories (PLM) in children, we know little about cases of adults and the impact of PLM on claimers. To fill these gaps, we investigated the profile of PLM adult claimers, features of PLM and associations with mental health, happiness, and religiosity/spirituality. We performed an online Brazilian national survey assessing sociodemographic data, PLM features, mental health, happiness, and religiosity/spirituality (R/S). We also performed adjusted regression models. Most of the sample (n = 402) was middle age 41.6 (SD 12.4) years, female (79%), with higher education (68%), Spiritists (54.5%) and very/moderately spiritual (91%). PLM started spontaneously in 82%, on average at 19.9 (SD 13.8) years old. Birthmark/defect (54%), unusual philia (30%) and phobia in childhood (71%), and persistent phobia (71%) were common associated features. Common mental disorders were frequent (46%), associated with an unusual philia OR3.99 (2.34, 6.99) and phobia in childhood OR2.60 (1.51, 4.57). Post-traumatic stress disorder (36%) was associated with phobia OR1.79 (1.07, 3.05). R/S was associated with higher happiness and lower mental disorders outcomes. PLM in adults and in children have similarities. The high prevalence of mental disorders symptoms needs to be better investigated, and R/S was a protective factor. The study highlights the importance of the investigation of PLM in adults, a neglected mental health issue.